APLIKASI E-COMMERCE MELALUI TELEPON SELULAR PADA PT. PRIMA MULTI SELULAR SEMARANG - Samiin Tarnomo; Ramadhan Riski (Jurnal Ilmiah Sistem Informasi, 2022)
Based on the survey conducted by the author at PT. Prima Multi Selular Semarang, the author tries to develop a system by utilizing an existing server in accordance with the required requirements, namely with a web-based ordering data system program with WAP-based ordering, using the ASP programming language: Active Server Pages. This change aims to make it easier for customers to order goods and increase the company's sales volume. In designing this new application, it also carries out several stages of making DFD, ERD and Normalization diagrams to describe data storage and relationships between data, determine tables to create programs and design input outputs. This stage is carried out as a tool to create a WAP-based ordering application program. WAP-based program is expected to be able to help problems related to PT. Prima Multi Selular. The program that is made, of course, still has several weaknesses and shortcomings, this is possible that the author's experience and knowledge in WAP programming problems is still possible. Suggestions and criticisms are very helpful for writers to develop knowledge in this field.